2022
DOI: 10.3389/fmicb.2022.877142
|View full text |Cite
|
Sign up to set email alerts
|

Probiotics for the Management of Infectious Diseases: Reviewing the State of the Art

Abstract: This review aims to provide insight into the potential of probiotics as a clinical modality targeted at infectious diseases by creating a comprehensive overview of the state of the art of research and development efforts as shown by patents and clinical trials of the past 20 years. Data were retrieved from patent and clinical trial databases to reflect the long- and short-term developments of probiotics research. The data were analyzed to extract information on the total number of patents and trials for each i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 54 publications
0
4
0
Order By: Relevance
“…Nowadays, a novel strategy for the management and prevention of numerous infectious illnesses is the use of bacterial probiotic strains and their metabolic products [10]. Probiotics from the Bacillus genus have been shown to exhibit antibacterial effects in experiments on animals [11,12].…”
Section: Introductionmentioning
confidence: 99%
“…Nowadays, a novel strategy for the management and prevention of numerous infectious illnesses is the use of bacterial probiotic strains and their metabolic products [10]. Probiotics from the Bacillus genus have been shown to exhibit antibacterial effects in experiments on animals [11,12].…”
Section: Introductionmentioning
confidence: 99%
“…Given the imbalance in the relatively slow production of new antimicrobials, from the pharmaceutical pipeline and the rapid development of AMR, new non-classical therapeutic options could be of great use in the fight against pathogens with significant AMR [128]. Several therapeutic strategies have been employed in this direction involving natural and chemical products, probiotics and prebiotics, antimicrobial peptides, bacteriophages, predatory bacteria, immunotherapy, vaccines, and other methods [10,11,[129][130][131][132][133]. Nanotechnology may offer valuable tools in this fight against pathogens harboring significant AMR.…”
Section: The Need For Non-antibiotic Interventions In the Treatment O...mentioning
confidence: 99%
“…For instance, certain strains of bacteria within the microbiome may enhance or inhibit the colonization and transmission of pathogens [211,212]. Understanding these dynamics can inform infection prevention strategies, such as the use of probiotics or targeted hygiene practices, to reduce the risk of disease transmission [89,213]. Additionally, studying the impact of the microbiome on treatment outcomes at a population level can help identify patterns and trends that guide public health interventions and resource allocation.…”
Section: Impact Of Microbiome On Treatment Outcomesmentioning
confidence: 99%
“…Probiotics have shown promise in preventing and treating various infectious diseases by restoring the balance of beneficial bacteria in the microbiome. For example, studies have demonstrated that certain strains of probiotics can reduce the duration and severity of gastrointestinal infections caused by pathogens such as C. difficile and Salmonella [213,249]. Another innovative approach involves the use of FMT, a procedure where fecal matter from a healthy donor is transferred to a recipient with a disrupted microbiome.…”
Section: Innovative Treatment Strategies Targeting the Microbiomementioning
confidence: 99%